CONSUMER ATTITUDE ON THE PEOPLE’S COFFEE OF PROCESSED ROBUSTA IN SOME REGENCIES OF JEMBER, LUMAJANG AND MALANG - Sri Tjondro Winarno; Darsono Darsono; Muhamad Harisudin; Sudiyarto Sudiyarto (UNEJ e-Proceeding, 2017)
Consumer has an important role in determining whether one product can attract him or notseen from several attributes available. This research aims at analyzing the main attributespossessed by processed product of people’s coffee ‘Robusta’ in several regencies of Jember,Lumajang and Malang. Meanwhile, the data required in this research were primary datawhich could be obtained by conducting a deep interview through questionnaire.Furthermore, this research was descriptive quantitative. The questionnaire was given to 180respondents of coffee’s consumers taken from the three regencies (Jember, Lumajang andMalang) employing accidental sampling method. The data obtained were then processed byemploying behavior’s method of consumer’s trust to multi attributes of Fishbein Model.Based on the data analysis, it showed that the highest score was aroma attribute (1,254), thentaste (1,106), obtaining easiness (0,804), price (0,739), packaging design (0,661), label(0,535), brand (0,527), storage length (0,452), packaging size (0,077), and the lowest wascolor’s sharpness (0,063). This result showed that the consumer of people’s coffee Robustawould prefer coffee’s aroma as their priority, taste, ease of obtaining, price, packaging designto the other attributes.